STATE POLICY MECHANISMS FOR STRENGTHENING THE SECURITY OF THE SOCIAL SPHERE OF UKRAINE IN THE FACE OF EXISTENTIAL CHALLENGES - Lupak, Ruslan (Current Problems of Sustainable Development, 2026)
The article develops scientific and applied recommendations for updating the complex of state policy mechanisms for strengthening the security of the social sphere of Ukraine in the face of existential challenges. The structural and institutional transformations of the social sphere caused by the full-scale military invasion, which led to the weakening of its security, are substantiated. The concept of mutual influences in the system of cause-and-effect events is formed: «consequences of military actions ↔ weakening of human social security ↔ destabilization of the social sphere, loss of its ability to self-reproduce». In accordance with the concept, dominant risks, threats and existential challenges for the social sphere of Ukraine are identified. The war includes a critical deterioration in the manageability of social processes caused by the destruction of social infrastructure and the destabilization of social institutions. Instead, the weakening of human social security in Ukraine has led to an increase in social vulnerability and deepening social inequality against the background of a decrease in the effectiveness of the system of social guarantees and limited social protection resources. An updated set of state policy mechanisms for strengthening the security of the social sphere of Ukraine is proposed, which includes institutional and adaptive, security and integration, infrastructure and restoration, coordination and partnership, information and monitoring, crisis management, economic and stabilization, social and protective, psychological and rehabilitation, digital and service, system and resilient, demographic and restoration, social and labor, institutional and organizational and strategic and predictive mechanisms. The expected effects of updating the set of state policy mechanisms for strengthening the security  of the social sphere in Ukraine are determined.
Keywords: social security; social sphere; public policy; social security of a person; existential challenges; mechanisms; risks and threats